(untitled) (Journal of Veterinary Medicine and Animal Production, 2021)
The present study was initiated to evaluate the effects of parity order and udder quarters on colostrum composition. The colostrum samples were collected from two different sites, the U. of K. dairy farm and Tamboul Camel Research Centre (TCRC). Six lactating cows at their 2nd, 4th, 5th, 7th, 9th and 10th parity together with two she camels both at their 3rd parity were selected from the U. of K. dairy herd. Three she camels at their 3rd, 4th and 5th parity were chosen from TCRC. Atotal of 66 colostrum samples were collected to represent the different parities, the three colostral days and the fore and rear udder quarters. The results revealed that parity order exerted different effects on the colostrum quality in the two species on colostrum quality. The cows colostrum contents of CP, TS and lactose were Sig. increased in the advanced parities (9-10). However in the she-camel colostrum only the CP content was favoured by advancing parities. The udder quarter effect on colostrum composition was not Sig in both species, however in the cow, the fore udder quarter colostrum was higher in all constituent except the fat. While in the she-camel the rear udder quarter excelled the fore udder colostrum samples in all constituents measured.